Breast cancer immunohistochemical features in young women with BRCA1/2 mutations - Zakhartseva, L.M.; Gorovenko, N.G.; Podolskaya, S.V.; Anikusko, N.F.; Lobanova, O.E.; Pekur, K.A.; Kropelnytskyi, V.A.; Shurygina, O.V. (Experimental Oncology, 2009)
Breast cancer among young women is a rare pathology. In most studies published so far, this patients group is not being analyzed separately. Particularities of this pathology require an additional examination of the immunohistochemical and molecular-genetic markers of the disease for development of the effective treatment protocols. The mutations of BRCA1/2 are the important factor impacting to the disease prognosis along the age of the patient. Aim: To compare the expression of prognostically meaningful immunohistochemical markers such as estrogen receptor (ER), progesterone receptor (PR), HER-2, p53, Ki-67, in tumor cells of the female patients with breast cancer aged less than 36 depending on the presence or absence of mutations in BRCA1/2 genes. Methods: Two hundred forty-eight patients aged less than 36 at the time of diagnosis of breast cancer were examined clinically. Expression of ER, PR, HER-2, p53, Ki-67 was determined by indirect immunohistochemical method. Mutations of BRCA1 (185delAG, 5382insC) and BRCA2 (6174delT) genes were screened using multiplex PCR in 99 patients. Results: Mutations of BRCA1/2 genes were found in 9.1% of patients. More aggressive clinical course of the disease was seen in mutations carriers, who had 3-years survival of only 55.6%. They did not demonstrated expression of ER, PR, and HER-2 in 88.9% of the cases. Whereas, patients without BRCA1/2 mutations did not express ER, PR, and HER-2 in only 42.0% of cases. There were no diffe rences between patients with and without mutations in terms of tumor size, presence of metastases in lymph nodes, p53 and Ki-67 expression. Conclusion: Presence of BRCA1/2 genes mutations in young women is associated with more aggressiveness of the breast cancer (their 3-years survival is 25, 5% less) and absence of the ER, PR, HER-2 receptors, which is unfavorable prognostic factor in terms of hormone therapy. These data should be taken into account at chemotherapy planning, especially in patients with early stages of the disease. There were no differences between patients with and without BRCA1/2mutations in terms of tumor size, lymph nodes involvement, tumor histology, and p53 and Ki-67 proteins expression.